DESARROLLO ECONÓMICO Y UNIVERSIDAD - Narváez Liceras, Alejandro (2007)
The competitiveness of the economy is the reflection of its productivity; and in consequence, it is the basis of its potential growth and the level of well-being of a nation. It is necessary to achieve a big capital endowment in order to increase the productivity. with more intensity in the factor work and the human capital formed by the education, abilities of people, the available use of the technologies, the capacity of the society to promote talent, facing risks, adopting innovations and creativity.